The Impact Of Go Green Operational Implementation On The Performance Of Msmes In Martapura - Wahyudi Wahyudi; Hidayatullah As-Syahri; Muhammad Saufi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
-